2017
DOI: 10.1126/scisignal.aah6037
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E 2 –EP2–NF-κB signaling in macrophages as a potential therapeutic target for intracranial aneurysms

Abstract: Intracranial aneurysms are common but are generally untreated, and their rupture can lead to subarachnoid hemorrhage. Because of the poor prognosis associated with subarachnoid hemorrhage, preventing the progression of intracranial aneurysms is critically important. Intracranial aneurysms are caused by chronic inflammation of the arterial wall due to macrophage infiltration triggered by monocyte chemoattractant protein-1 (MCP-1), macrophage activation mediated by the transcription factor nuclear factor κB (NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
179
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(193 citation statements)
references
References 60 publications
12
179
0
2
Order By: Relevance
“…), this PG cascade is considered as a major mediator of acute inflammation. In addition to such a traditional concept, recent experimental findings including ours have suggested the crucial role of PG cascade in formation and exacerbation of chronic inflammation promoting the IA pathogenesis [5,7]. In brief, NF-κB activation, a hallmark of inflammation in IA lesions [8], can be detected in infiltrating macrophages and endothelial cells in IA lesions of mouse model at the early stage and, later on, spreads to entire arterial walls.…”
Section: Editorialmentioning
confidence: 92%
See 1 more Smart Citation
“…), this PG cascade is considered as a major mediator of acute inflammation. In addition to such a traditional concept, recent experimental findings including ours have suggested the crucial role of PG cascade in formation and exacerbation of chronic inflammation promoting the IA pathogenesis [5,7]. In brief, NF-κB activation, a hallmark of inflammation in IA lesions [8], can be detected in infiltrating macrophages and endothelial cells in IA lesions of mouse model at the early stage and, later on, spreads to entire arterial walls.…”
Section: Editorialmentioning
confidence: 92%
“…In addition, such a factor may be applicable to develop drugs for many other macrophage-related diseases. As described in greater detail below, we have recently identified Sphingosine-1-phosphate receptor type 1 (S1P 1 ) and PGE receptor subtype 2 (EP2) as a strong therapeutic target [5,6] (Figure 1).…”
Section: Targeting Macrophages To Treat Intracranial Aneurysm Tomohirmentioning
confidence: 99%
“…Aoki et al . identified the PGE 2 ‐EP 2 ‐NF‐κB signalling cascade in macrophages infiltrating the arterial wall as a factor sustaining the pathogenesis of IA and making the inflammation chronic (Aoki et al ., ). They found that PGE 2 activates NF‐κB synergistically with TNF‐α via EP 2 receptors in macrophages in vitro to induce pro‐inflammatory genes including COX‐2 and the macrophage chemokine CCL2 (also called MCP‐1) and that CCL2 mRNA is also stabilized by this pathway.…”
Section: Pg‐cytokine Crosstalk In Myeloid and Stromal Cell‐mediated Cmentioning
confidence: 97%
“…They found that PGE 2 activates NF‐κB synergistically with TNF‐α via EP 2 receptors in macrophages in vitro to induce pro‐inflammatory genes including COX‐2 and the macrophage chemokine CCL2 (also called MCP‐1) and that CCL2 mRNA is also stabilized by this pathway. Consistent with these in vitro findings, mice with macrophage‐specific EP 2 receptor deletion or with transgenic expression of an IκB mutant that restricts NF‐κB activation showed reduced IA incidence with fewer infiltrated macrophages (Aoki et al ., ). Similarly, administration of an EP 2 antagonist in a rat model of IA reduced macrophage infiltration and suppressed IA formation and progression (Aoki et al ., , ).…”
Section: Pg‐cytokine Crosstalk In Myeloid and Stromal Cell‐mediated Cmentioning
confidence: 97%
“…Increased expression of inflammatory mediators such as matrix metalloproteases-9, nuclear factor κB (NF-κB), and tumor necrosis factor-α through the stabilization of inhibitor κB have been listed [13-16], and considered the targets for pharmacological stabilization of intracranial aneurysms. Those include non-steroidal anti-inflammatory drugs, statins, angiotensin-converting enzyme-inhibitors, angiotensin II receptor blockers, NF-κB decoy, and inhibitors of protease such as MMP, and tetracyclines [17].…”
Section: Discussionmentioning
confidence: 99%